A physics-informed approach for post-event regional diagnosis of arch dam cracking - Ruiqi Wu; Xiaohu Du; Ziwei Li; Huijun Qi; Tongchun Li; Chaoning Lin (Engineering Structures, 2026)

Size matching between laccase and carrier via tunable diamine-derived flexible spacer arms for enhanced phenolic wastewater degradation - Jie Zhang; Yiqi Gong; Zhipeng Qin; Xinyi Liu; Jiao Yu; Tao Feng; Wan Zhang; Wenjing Lin; Kaiyue Kang; Xuemei Tan; Lin Zhuo; Ruiqi Wang; et al. (Journal of Water Process Engineering, 2026)

A novel geochemical enhanced measurement while drilling method for adverse geology identification: GE-MWD - Zhenhao Xu; Jintao Kang; Peng Lin; Ruiqi Shao; Huihui Xie (International Journal of Rock Mechanics and Mining Sciences, 2026)

Biodegradation of potassium amyl xanthate from mining flotation wastewater with minimal CS2 emission - Yuhang Cai; Jingyuan Zhai; Meiqi Lin; Wanyu Huang; Ruiqi Zhang; Chen-Wei Zheng; Yi-Hao Luo; Bruce E. Rittmann (Journal of Hazardous Materials, 2026)

Occurrence, variation and risks of viruses in aerosols during rural wastewater collection, treatment and discharge - Yingming Zhu; Su Xu; Yu Zhou; Ruiqi Quan; Jun Zhan; Xuesong Guo; Lin Li; Junxin Liu (Journal of Cleaner Production, 2026)

Quantitative analysis of spray morphology and shock wave structures in supercritical methanol spray - Xiaojie Li; Liang Wang; Yi Hu; Lin Xiang; Ruiqi Wang; Qi Xiao; Zhaowen Wang (Fuel, 2026)

Regional variations and dynamic coordination mechanisms in the coupling of new-type urbanization with agricultural and rural modernization - Xinmin Liu; Yutong Leng; Ruiqi Liu; Kangkang Lin (Environment, Development and Sustainability, 2026)

Bacillus velezensis-fermented postbiotics as feed additives for viral infection control in largemouth bass (Micropterus salmoides) - Gaofeng Cheng; Zhihao Jiang; Shun Li; Ruiqi Lin; Xinyou Wang; Yong Shi; Xiaoyun Chen; Zhen Xu; Weiguang Kong (Fish & Shellfish Immunology, 2026)

Immunoglobulin M response in different intestinal segments of largemouth bass (Micropterus salmoides) following largemouth bass virus (LMBV) infection - Xinyou Wang; Gaofeng Cheng; Jie Sun; Chang Cai; Zhihao Jiang; Ruiqi Lin; Shun Li; Li Li; Juan Zhao; Zhen Xu; Weiguang Kong (Fish & Shellfish Immunology, 2026)

Rapid and high-capacity adsorption of malachite green based on recoverable amino-modified HOF systems - Yile Jiang; Xinyan He; Ruiqi Zhu; Qiuxia Wu; Lin Zhang; Yabing He; Dian Zhao (Journal of Environmental Sciences, 2026)

Efficient self-accelerated degradation of polyester enabled by encapsulated enzymes for closed-loop recycling - Ruiqi Bao; Ning Zheng; Zhenchao Zhou; Tariq Mehmood; Xinyi Shuai; Zejun Lin; Hong Chen (Chemical Engineering Journal, 2026)

Crude oil biodegradation by synthetic microbial consortia: Performance and mechanisms under a top-down enrichment strategy - Wenya Wang; Qing Xiao; Ruiqi Lin; Hao Zhou; Yuanyuan Qu; Jingjing Zhan; Xuwang Zhang (Journal of Environmental Chemical Engineering, 2026)

Interfacial structure and adsorption at hydrogen–brine interfaces regulated by cushion gases (N2, CO2): A molecular dynamics simulation - Pengyu Chen; Riyi Lin; Shengxiang Ma; Huanan Li; Yujie Fu; Qiwei Donga; Ruiqi Liu; Zhizhuang Wang; Chengxing Huang; Yan Qiao (Fuel, 2026)

Surface-displayed MCP-3 vaccine in Bacillus subtilis elicits protective immune responses against LMBV infection in largemouth bass - Ruiqi Lin; Zhihao Jiang; Qianqian Zhang; Shun Li; Xueying Qin; Xinyou Wang; Gaofeng Cheng; Zhen Xu; Weiguang Kong (Fish & Shellfish Immunology, 2026)

An efficient strategy to separate nanoplastics from water using anisotropic magnetic Janus particles - Ruiqi Yan; Sen Lin; Xia Yu; Lei Zhang; Jiaxi Wang; Wentao Zhao; Mingyang Xing; Qian Sui (Water Research, 2026)

An enhanced sorting method for second-life lithium-ion batteries based on two-step clustering - Fu Wan; Yupeng Lin; Da Yang; Shufan Li; Ruiqi Liu; Lei Zhu; Wenwei Yin; Weigen Chen (Journal of Cleaner Production, 2026)

Screening key protective antigens of largemouth bass virus and evaluation of their immunoprotective efficacy - Zhihao Jiang; Ruiqi Lin; Gaofeng Cheng; Xueying Qin; Xinyou Wang; Yong Shi; Qianqian Zhang; Weiguang Kong; Zhen Xu (Fish & Shellfish Immunology, 2026)

SREBP2 confers ferroptosis resistance by targeting GPX4 in colorectal cancer - Huage Zhong; Ruiqi Chen; Tianyu Chen; Min Lin; Siqi Wen; Man Zhang; Dejun Liu; Junfeng Yu; Jinchi Chen; Bei Yi; Rong Liang; Wei Jiang; et al. (Apoptosis, 2026)

AFP-GFuse: an antifungal peptide identification model with structural information fusion via multi-graph neural networks and cross-attention mechanism - Xiaomeng Lin; Ruiqi Liu; Aoyun Geng; Junlin Xu; Yajie Meng; Feifei Cui; Leyi Wei; Quan Zou; Zilong Zhang (Molecular Diversity, 2025)

Sustainable recycling of spent graphite anodes: The critical role of thermal-assisted organic acid leaching in structural and performance restoration - Fu Wan; Wenwei Yin; Da Yang; Kaida Hu; Ruiqi Liu; Yupeng Lin; Weigen Chen (Journal of Environmental Chemical Engineering, 2025)

Characterization of flavor profile and microbial community dynamics in naturally fermented sour watermelon - Lin Zhang; Dengcheng Li; Lijuan Zhou; Liping Zhu; Ruiqi Zhang; Qiongping Hong; Sixin Liu; Congfa Li (Food Research International, 2025)

Regulating a P-rich SEI via a phosphoryl MOF-based quasi-solid electrolyte for dendrite-free Li metal batteries - Dongze Li; Siyuan Shao; Xiaoyan Lin; Kun Yao; Shaoru Chen; Donghui Cai; Yingxin Wu; Yanting Zhou; Ruiqi Li; Ziqi Wang (Chemical Engineering Journal, 2025)

Late Holocene extreme dust events in the arid Central Asia recorded by lake sediments in Tien Shan - Min Zheng; Xiaozhong Huang; Ning Wang; Menghan Qiu; Jun Zhang; Lixiong Xiang; Shaojun Chen; Muhammad Farqan; Ruiqi Min; Tao Wang; Chong Huang; Xiuxiu Ren; et al. (Quaternary Science Reviews, 2025)

Unlocking biochar's carbonyl group: Fe-Mn oxide synergy enables high-efficiency As(III) immobilization via non-radical oxidation - Zihang Cheng; Yilin Wu; Ruiqi Du; Mingming Lin; Jingzi Beiyuan; Juan Liu; Peng Liu; Bowen Li; Xueding Jiang; Hailong Wang (Journal of Environmental Management, 2025)

High-entropy Fe-based spinel oxide for simultaneous electrochemical desalination and dye adsorption in textile wastewater remediation - Ruiqi Yong; Ying Zhao; Chuhan Huang; Pengrui Sun; Wei Zhou; Tianqin Huang; Yuqi Wei; Karunaivel Kajanann; Kailin Fan; Kun Lin; Yiyi Wang; Lifeng Ding; et al. (Chemical Engineering Journal, 2025)

Floodplain hydrodynamics and connectivity in a natural compound channel during unsteady flow events - Jiaming Liu; Yang Xiao; Saiyu Yuan; Taotao Zhang; Qingwei Lin; Kang Yuan; Ruiqi Wang; Carlo Gualtieri (Journal of Hydrology, 2025)

Full-scale studies are closer to reality than lab-scale ones: Tertiary treatment constructed wetlands maintain robust removal capability for pharmaceuticals and personal care products in cold weather conditions - Jiaxi Wang; Beibei Ye; Xia Yu; Ruiqi Yan; Hui Lin; Ying Man; Qian Sui (Bioresource Technology, 2025)

Developmental toxicity and environmental risk assessment of chlorothalonil: A comprehensive study using biomphalaria as a model gastropod - Hongyu Li; Ruiqi Weng; Hao Wu; Xianwei Li; Jiyuan Wang; Jialu Xu; Qingzhi Zhao; Yunhuan Zhu; Yuncheng Qian; Yijie Zhang; Xiaofen Zhang; Lijun Lin; et al. (Journal of Hazardous Materials, 2025)

Machine Learning of Element Geochemical Anomalies for Adverse Geology Identification in Tunnels - Ruiqi Shao; Peng Lin; Zhenhao Xu; Fumin Liu; Yilong Liu (Journal of Earth Science, 2025)

Comprehensive analysis of microplastics at typical outlets around Hainan Island: From spatial distribution to flux estimation and correlation analysis - Shiyu Xie; Yuanyuan Su; Dan Qi; Fei Liu; Liu Gao; Ruiqi Bao; Xing Cheng; Xubing Lin; Tingting Zhang; Licheng Peng (Water Research, 2025)

Research on digital twin-based dynamic evolution model for the reactor hull structure of an icebreaker - Yi Lin; Siyuan Liu; Lizhi Chen; Ruiqi Cheng; Zhiyong Pei (Ocean Engineering, 2025)

Uptake of plasmid reduces the adaptation of Shigella flexneri to disinfectants and increases transmission of antibiotic resistance genes - Xiaojun Lin; Ruiqi Han; Huishi Peng; Junwei Huang; Yanbin Xu; Qingxia Qiao; Lu Huang (International Biodeterioration & Biodegradation, 2025)

Multi-omics joint analysis: Pachymic acid ameliorated non-alcoholic fatty liver disease by regulating gut microbiota - Guilin Ren; Yiyou Lin; Yilong Fu; Fucai Liu; Ruiqi Wang; Congcong Zhang; Jiannan Qiu; Lin Chen; Xiaobing Dou (Food Research International, 2025)

Study on the pathways of thermochemical sulfate reduction between sulfates and alkanes at low temperatures - Yiya Wang; Liqiang Zhang; Chuantao Zhu; Riyi Lin; Xinlu Han; Kunlun Xie; Ruiqi Liu; Jinyu Li; Chenxing Huang; Qiwei Dong; Xinwei Wang (Fuel, 2025)

Transcriptome sequencing promotes insights on the molecular mechanism of SKP-SC-EVs mitigating denervation-induced muscle atrophy - Junfei Lin; Yong Cai; Jian Wang; Ruiqi Liu; Chong Qiu; Yan Huang; Boya Liu; Xiaoming Yang; Songlin Zhou; Yuntian Shen; Wei Wang; Jianwei Zhu (Molecular Biology Reports, 2024)

Cataclastic deformation and alteration induced fault water inrush: Cross effect, hazard characteristics and identification method - Ruiqi Shao; Zhenhao Xu; Peng Lin (Tunnelling and Underground Space Technology, 2024)

Postharvest ripening improves the texture and active ingredients of noni fruit (Morinda citrifolia L.) for processing - Ruiqi Zhang; Qiongping Hong; Dengcheng Li; Lijuan Zhou; Xinjun Wang; Ruimin Wang; Sixin Liu; Lin Zhang; Congfa Li (Postharvest Biology and Technology, 2024)

A conical spiral methanol steam reforming reactor for spectral splitting-based concentrating photovoltaic-thermochemical hybrid production - Riyi Lin; Jinyu Li; Yi Ge; Yiya Wang; Pengyu Chen; Huanan Li; Qiwei Dong; Ruiqi Liu; Chenxing Huang; Xinwei Wang; Zhengda Yang (Journal of Cleaner Production, 2024)

Glutathione‑iron hybrid nanozyme-based colorimetric sensor for specific and stable detection of thiram pesticide on fruit juices - Xu Yan; Ruiqi Zou; Qiqi Lin; Yuan Ma; Aixin Li; Xun Sun; Geyu Lu; Hongxia Li (Food Chemistry, 2024)

Effects of disposable face mask microplastics on soil properties and microbial communities - Liping Lin; Gongren Hu; Yangzi Lijin; Luowei Gan; Ruiqi Zhang; Ling Wang; Changhao Lu; Jianping Gao; Jiatai Lin; Le Yang; Yu Yan; Ruilian Yu (CATENA, 2024)

Research on Collapse Testing of Nuclear Icebreaker Reactor Hull Structure Based on Distortion Similarity Theory - Yi Lin; Ruiqi Cheng; Lizhi Chen; Xiangshao Kong; Zhiyong Pei (Journal of Marine Science and Engineering, 2024)
In this study, the finite element method combined with the model test method are used to investigate the ultimate strength of a target ship reactor hull structure under a pure bending load. Based on the distortion similarity theory and nonlinear similarity method, a scale model of the actual ship reactor hull structure is designed and the model collapse test is conducted. The ultimate bending moment obtained by the model test is transformed to the actual ship through the similarity transformation relationship and compared with the nonlinear finite element analysis result of the actual structure. The results are consistent with each other, which indicates that the collapse characteristics of the actual ship reactor hull structure can be better forecasted using the model test results when the test model is designed based on the nonlinear similarity method and distortion similarity theory.

Landscape of plasmids encoding β-lactamases in disinfection residual Enterobacteriaceae from wastewater treatment plants - Zejun Lin; Zhenchao Zhou; Xinyi Shuai; Guangshu Zeng; Ruiqi Bao; Hong Chen (Water Research, 2024)

Effects of polypropylene microplastics on carbon dioxide dynamics in intertidal mangrove sediments - Xubing Lin; Shuying Lin; Licheng Peng; Miao Chen; Xing Cheng; Shiyu Xie; Ruiqi Bao; Yuanyuan Su; Tariq Mehmood (Environmental Pollution, 2024)

3D Models of Sarcomas: The Next-generation Tool for Personalized Medicine - Ruiling Xu; Ruiqi Chen; Chao Tu; Xiaofeng Gong; Zhongyue Liu; Lin Mei; Xiaolei Ren; Zhihong Li (Phenomics, 2024)

Celecoxib attenuates hindlimb unloading-induced muscle atrophy via suppressing inflammation, oxidative stress and ER stress by inhibiting STAT3 - Yanan Ji; Junfei Lin; Ruiqi Liu; Kexin Wang; Mengyuan Chang; Zihui Gao; Boya Liu; Yuntian Shen; Jianwei Zhu; Xinlei Yao; Lei Qi; Hualin Sun (Inflammopharmacology, 2024)

In vitro assessment of the bacterial stress response and resistance evolution during multidrug-resistant bacterial invasion of the Xenopus tropicalis intestinal tract under typical stresses - Xiaojun Lin; Ruiqi Han; Taojie Liang; Chaonan Zhang; Yanbin Xu; Huishi Peng; Xiao Zhou; Lu Huang (Journal of Hazardous Materials, 2024)

Identification of algicidal monoterpenoids from four chemotypes of Cinnamomum camphora and their algicidal mechanisms on Microcystis aeruginosa - Tianyu Huang; Meng Lai; Zhenwei Lin; Ruiqi Luo; Xuezheng Xiang; Haozhe Xu; Ning Pan; Zhaojiang Zuo (Environmental Research, 2024)

Effect of aggregation behavior on microplastic removal by magnetic Fe3O4 nanoparticles - Ruiqi Yan; Sen Lin; Weinan Jiang; Xia Yu; Lei Zhang; Wentao Zhao; Qian Sui (Science of The Total Environment, 2023)

Unveiling the treatment-driven secondary risks of pharmaceuticals: New lessons from calcium channel blocker transformation by multiple oxidants - Linke Jiang; Ruiqi Wang; Jieru Lin; Wenzheng Chen; Mingbao Feng (Science of The Total Environment, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

Heterogeneous aggregation between microplastics and microalgae: May provide new insights for microplastics removal - Yuanyuan Su; Liu Gao; Licheng Peng; Xiaoping Diao; Shengyou Lin; Ruiqi Bao; Tariq Mehmood (Aquatic Toxicology, 2023)

Fe/Ni layered double hydroxide biocatalysts inhibit tumor growth through ROS and ferroptosis signaling pathway - Qiwen Pan; Fei Lin; Ruiqi Liu; Yilin Li; Xinyue Zhang; Rui Luo; Lingling Cai; Yang Liu; Wuguo Deng; Liru He (Chemical Engineering Journal, 2023)

Totally-green cellulosic fiber with prominent sustained antibacterial and antiviral properties for potential use in spunlaced non-woven fabric production - Jinxin Lan; Yao Wu; Changmei Lin; Jiazhen Chen; Ruiqi Zhu; Xiaojuan Ma; Shilin Cao (Chemical Engineering Journal, 2023)

Research of Intelligent Logistics and High-Quality Economy Development for Yangtze River Cold Chain Shipping Based on Carbon Neutrality - Ruiqi Xiao; Lin Pan; Hanbin Xiao; Han Xiao; Ze Zhu (Journal of Marine Science and Engineering, 2022)
The current status of intelligent logistics and cold chain shipping research is a hot topic worldwide. Meanwhile, the study of regional logistics and regional economy, shipping logistics and regional economic theory and application methods, and the empirical analysis of the correlation between the Yangtze River shipping and the Yangtze River shipping economy have attracted a lot of attention. This research has revealed that the Internet of Things of Yangtze River shipping has a great impact on the Yangtze River and the importance of inland river economic development. This study presents the empirical analysis on the correlation between shipping logistics and the inland river economy, starting from qualitative and quantitative aspects, and taking Yangtze River shipping as the representative. The proposed mathematical models and qualitative data analysis are made on the relevant effects of intelligent logistics and cold chain shipping on an inland river economy including its impact on the industrial layout, international trade, and urbanization. The research results provide administrative decisions or guidance values for the economic development of inland river ports in the Yangtze River.

Geochemical, mineralogical, and microstructural characteristics of fault rocks and their impact on TBM jamming: a case study - Peng Lin; Tengfei Yu; Zhenhao Xu; Ruiqi Shao; Wenyang Wang (Bulletin of Engineering Geology and the Environment, 2022)

Risk assessment of TBM jamming based on Bayesian networks - Peng Lin; Yue Xiong; Zhenhao Xu; Wenyang Wang; Ruiqi Shao (Bulletin of Engineering Geology and the Environment, 2022)

Rabies Virus Pseudotyped with CVS-N2C Glycoprotein as a Powerful Tool for Retrograde Neuronal Network Tracing - Xutao Zhu; Kunzhang Lin; Qing Liu; Xinpei Yue; Huijie Mi; Xiaoping Huang; Xiaobin He; Ruiqi Wu; Danhao Zheng; Dong Wei; Liangliang Jia; Weilin Wang; et al. (Neuroscience Bulletin, 2020)